Exosome trapping and enrichment using a sound wave activated nano-sieve (SWANS). Issue 19 (9th September 2020) - Habibi, Ruhollah; He, Vincent; Ghavamian, Sara; de Marco, Alex; Lee, Tzong-Hsien; Aguilar, Marie-Isabel; Zhu, Dandan; Lim, Rebecca; Neild, Adrian
Abstract : Mechanically activated packed-bed of beads (SWANS) traps and rapidly enriches the concentration of exosomes, a form of extracellular vesicles, while preserves the integrity of the lipid bilayer membrane. Also, larger beads perform better in capturing. Abstract : Exosomes, a form of extracellular vesicle, are an important precursor in regenerative medicine. Microfluidic methods exist to capture these sub-micrometer sized objects from small quantities of sample, ideal for multiple diagnostic applications. To address the challenge of extraction from large volumes, we use the visual access offered by microfluidic techniques to probe the physical mechanisms behind a method which is compatible with future upscaling. The sound wave actuated nano-sieve uses resonant modes in a packed bed of microparticles to exert trapping forces on nanoparticles. Here, we examine the role of the microparticle size, demonstrating better performance from 15 μm particles than 7 μm particles. When applied to biological samples, we demonstrate for the first time that a packed bed of these larger particles is capable of capturing exosomes and liposomes, the captured particles being on average 20 to 40 times smaller than the pores within the trapped bed.